PENERAPAN PEMBERIAN REWARD TERHADAP MINAT BELAJAR SISWA SEKOLAH DASAR KELAS VI TENTANG PENDIDIKAN JASMANI - Nyoman Wali, Carles (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
Education is the path to a bright life after darkness and education has a very important role in educating humans on this earth. The aim of this research is to determine students' interest in the learning process based on the application of giving rewards to students at SDI Sikumana, East Nusa Tenggara. The method used in this research is quasi-experimental research. The data collection technique in this research is a questionnaire. The sampling technique uses cluster sampling technique. The population in this study was all students in class VIA and Class VIB with a total of 70 students with a breakdown of 35 students in each class. The sample in this research was 70 students. Analysis techniques in quantitative descriptive research with prerequisite test principles. The results of this study prove that there is a very significant difference in the application of rewards in the learning process of physical education, health and recreation. This is based on the results of the t test with a significance value of 0.021 0.05. So it can be concluded that the application of giving rewards triggers increased student interest in the learning process.